Entrepreneurial Aptitude of Women of an Aspirational District of Uttarakhand (Indian Journal of Extension Education, 2023)
A cross-sectional study was conducted for assessing the entrepreneurial aptitude of women in two blocks (Kashipur and Gadarpur) of Udham Singh Nagar, Uttarakhand. A purposive sampling technique was utilized for selecting the respondents. A structured questionnaire vetted by experts and pretested through a pilot study on 45 respondents was developed. Data on women entrepreneurs, self-assessment, and perception of farm women regarding entrepreneurial aptitude was collected from 214 women during the month of June 2022 to August 2022. Results revealed that only 28.50 per cent of women were running their own enterprises, whereas 40.98 per cent of them were engaged in vegetable production/commercial farming. 89.25 per cent of women were interested in running an enterprise and 84.11 per cent had a motto to earn money. 84.11 per cent of the respondents were interested in backyard poultry and 31.31 per cent in spice production. It was concluded that women in the study area had an aptitude for adopting enterprises for improving their quality of life, which needs to be nurtured.